2018
DOI: 10.3389/fmicb.2018.01142
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Beijing Douzhir Microbiota by High-Throughput Sequencing and Isolation of Acidogenic, Starch-Flocculating Strains

Abstract: Beijing Douzhir is a traditional Chinese fermented drink produced by the natural fermentation of mung beans as the raw material. Ma tofu is an edible by-product of Douzhir processing. Douzhir microbiota, particularly bacteria involved in the natural fermentation process, has not been clearly established, resulting in limited industrial Douzhir production. Here, three uncooked Douzhir samples (D group) and three uncooked Ma tofu samples (M group) (two replicates per sample) were collected from three manufacture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Accordingly, a strain of Lactococcus lactis subsp . lactis YM313 screened from Beijing Douzhir which had excellent fermentation flavor ( Xu et al, 2018 ) and a strain of Lacticaseibacillus casei YQ336 screened from soybean acid slurry which could rapidly produce acid ( Xu et al, 2019 ) were used as a starter culture for TBS fermentation. The volatile flavor substances changes in TBS and Bian-Que Triple-Bean Soup after fermentation (FTBS) were analyzed by SPME-GC–MS and electronic nose.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a strain of Lactococcus lactis subsp . lactis YM313 screened from Beijing Douzhir which had excellent fermentation flavor ( Xu et al, 2018 ) and a strain of Lacticaseibacillus casei YQ336 screened from soybean acid slurry which could rapidly produce acid ( Xu et al, 2019 ) were used as a starter culture for TBS fermentation. The volatile flavor substances changes in TBS and Bian-Que Triple-Bean Soup after fermentation (FTBS) were analyzed by SPME-GC–MS and electronic nose.…”
Section: Introductionmentioning
confidence: 99%
“…Xu Qiong et al [9] used HTS to sequence the genes in the 16 SrDNAV1-V3 regions of the Hongqu sufu strain to analyze the bacterial diversity in Hongqu sufu in different regions, and the research deepened the understanding of bacterial community composition and diversity in Hongqu sufu. Many studies have applied this technique to the analysis of microbial diversity during fermentation, such as in tempeh [10], bean juice [11], miso [12], Qula [13], and so on. In terms of research on sufu flavor compounds, Ran Chunxia et al reported the following finding [14]: the extraction and analysis of volatile compounds of sufu by headspace solid-phase microextraction gas chromatography-mass spectrometry technology combined with headspace solid-phase microextraction gas chromatography-mass spectrometry (HS-SPME-GC-MS) technology indicates that HS-SPME-GC-MS technology is most mature for the analysis of flavor compounds in sufu.…”
Section: Introductionmentioning
confidence: 99%